2016
DOI: 10.3390/rs8120986
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Sentinel Satellites for Burnt Area Mapping and Monitoring in the Congo Basin Forests

Abstract: Abstract:In this study, the recently launched Sentinel-2 (S2) optical satellite and the active radar Sentinel-1 (S1) satellite supported by active fire data from the MODIS sensor were used to detect and monitor forest fires in the Congo Basin. In the context of a very strong El Niño event, an unprecedented outbreak of fires was observed during the first months of 2016 in open forests formations in the north of the Republic of Congo. The anomalies of the recent fires and meteorological situation compared to his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 53 publications
(80 reference statements)
5
91
1
2
Order By: Relevance
“…Consequently, the exotic herb species Chromolaena odorata, which is very abundant along open roads in central Africa, disappeared shortly after road abandonment due to growth of taller shading species (Kleinschroth et al 2016c). In the Congo Basin, recent El Niño-related fire events showed a clear positive correlation with the abundance of Marantaceae herbs (Verhegghen et al 2016). These indigenous herbs show long-lasting high abundance on abandoned logging roads (Kleinschroth et al 2016c), which may explain many (but not all) observed fire outbreaks being located near permanent or recently abandoned logging roads in this region (Verhegghen et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, the exotic herb species Chromolaena odorata, which is very abundant along open roads in central Africa, disappeared shortly after road abandonment due to growth of taller shading species (Kleinschroth et al 2016c). In the Congo Basin, recent El Niño-related fire events showed a clear positive correlation with the abundance of Marantaceae herbs (Verhegghen et al 2016). These indigenous herbs show long-lasting high abundance on abandoned logging roads (Kleinschroth et al 2016c), which may explain many (but not all) observed fire outbreaks being located near permanent or recently abandoned logging roads in this region (Verhegghen et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In the Congo Basin, recent El Niño-related fire events showed a clear positive correlation with the abundance of Marantaceae herbs (Verhegghen et al 2016). These indigenous herbs show long-lasting high abundance on abandoned logging roads (Kleinschroth et al 2016c), which may explain many (but not all) observed fire outbreaks being located near permanent or recently abandoned logging roads in this region (Verhegghen et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of new perspectives and methods is illustrated by recent research, exploiting the potential of Sentinels data for forest characterization, such as new methods for forest deforestation, degradation, and fire monitoring; 43,44 new detailing of canopy in terms of biophysical properties or for functional types classification; 45,46 and innovative data fusion for mapping plantation extent. 47 Very few studies addressed the applicability of S1, S2, or joint data, for biomass monitoring.…”
Section: Introductionmentioning
confidence: 99%